Stillbirth and Neonatal Mortality in Pregnancies Complicated by Major Congenital Anomalies: Findings From a Large European Cohort. Issue 3 (March 2018) - Groen, Henk; Bouman, Katelijne; Pierini, Anna; Rankin, Judith; Rissmann, Anke; Haeusler, Martin; Yevtushok, Lyubov; Loane, Maria; Erwich, Jan Jaap H. M.; de Walle, Hermien E. K.
Abstract : (Abstracted from Prenat Diagn 2017;37:1100–1111) Modern ultrasound technology has revolutionized prenatal screening and provided women with a means of obtaining clinical information that can help inform their decision making about their pregnancy through detection of congenital anomalies (CAs). Not all CAs are detectable in the gestational window where abortion is legally allowed.